Physical properties and organic carbon content of a Typic Hapludult soil fertilised with pig slurry and pig litter in a no-tillage system - Comin J.J. (2013)
Applications of swine residues to the soil surface in a no-tillage system (NTS) may increase the organic carbon level and improve the physical properties of the soil. This study aimed to evaluate the effect of the continuous application of pig slurry (PS) and pig litter (PL) on the total organic carbon (TOC) content and physical properties of soil under NTS in Southern Brazil. In March 2010, after 8 years of cultivation of black oats (Avena strigosa)-maize (Zea mays), soil samples were collected in the 0-5, 5-10, 10-15, and 15-20cm layers. The treatments consisted of a control plot (without manure application), plots with PS applications equivalent to one and two times the recommended rate of nitrogen (N) for maize and black oats (PS1X and PS2X, respectively), and plots with PL equivalent to one and two times the recommended rate of N for maize and black oats (PL1X and PL2X, respectively). The TOC, soil bulk density (BD), penetration resistance (PR), total porosity (TP), macro- and microporosity, distribution of pore diameters, and indices of aggregation and aggregate stability were evaluated. Differences were found between treatments for TOC, BD, macro- and microporosity, pore diameter, aggregation, and PR. Treatment with PL favoured the production of aggregates (diameter >4mm) and increased the rates of aggregation and aggregate stability in the 10-15 and 15-20cm layers and macroporosity in the 0-5 and 15-20cm layers. Application of PL2X reduced PR by 34% and 20%, respectively, in the 5-10 and 10-15cm layers. Eight years of adding PS to successive cultivations of black oats-maize soil managed under NTS produced no changes in the physical features or the TOC of the soil, whereas the application of PL produced improvements in physical attributes of the soil and increased soil TOC. © CSIRO 2013.